Financial sector: Banks fall behind and now have a lower proportion of women on executive and advisory boards than insurance companies - Elke Holst; Katharina Wrohlich (DIW Economic Bulletin, 2017)
Women are still in the clear minority among the financial sector's top decision-making bodies. According to DIW Berlin's Women Executives Barometer, at the end of 2016, 21 percent of the supervisory and administrative board members of the 100 largest banks were female. The number has stagnated compared to last year. Since 2010, when the discussion about the gender quota for supervisory boards gained momentum, growth has been relatively flat - particularly in comparison to the top 100 companies outside the financial sector. At insurance companies, the proportion of women on supervisory boards was a solid 22 percent (an increase of around three percentage points). This puts insurance companies ahead of banks for the first time since 2006. Also of note: companies whose supervisory boards contained one-third women were not able to increase this number in 2016. Extrapolating from the past decade, supervisory boards of banks would need 50 years for the ratio of women to men to be equal. Gender parity in executive boards would be reached in 80 years. The proportion of women on executive boards remained very low overall as it reached roughly ten percent at insurance companies and eight percent at banks.
Keywords: G2; J16; J78; L32; M14; M51; 330; board composition; board diversity; boards of directors; central banks; corporate boards; Europe; finance industry; financial sector; female directors; gender gap; gender equality; gender quota; Germany; insurance companies; management; public and private banks; supervisory boards; women CEOs